HAWKING TEMPERATURE IN SCHWARZSCHILD BLACK HOLES WITH QUINTESSENCE DARK ENERGY - Widiyani, Agustina; Sari, Ana Novita; Permanasari, Ikah Ning Prasetiowati; Satria, Eko; Pohan, Azrul Sulaiman Karim; Kesuma, Weni Ayu Puja; Pardede, Indra; Suroso, Agus (Indonesian Physical Review, 2025)
Black holes are thermodynamic objects that emit Hawking radiation near the event horizon of a black hole according to the theory of quantum gravity in curved space-time. This radiation is manifested as the temperature of a black hole, known as the Hawking temperature. According to black hole thermodynamics, the black hole horizon area corresponds to the entropy. The increase in the horizon area is predicted due to the influence of dark energy, which can push the horizon of the black hole away from its center, thus significantly affecting the radiation of the black hole. Here, we investigate the Hawking temperature of the Schwarzschild black hole under the effect of quintessence dark energy. The results show that the increase in quintessence reduces the horizon radius of the black hole and lowers its Hawking temperature, highlighting the direct relationship between dark energy and black hole dynamics.